(3GdNW GdYQHj (B- (3fXQjI LeGdjI hMQaI jOhjI (B/s - Shaker Laibi; (3TGcQ dYjHjs ((3GdTGQbI;s (3OGFQI GdKbGaI h GdESdGe;s, 2007)
(3efJOi GdESdGe (B@ 12-30 (3CHQjd (B2014 (3GdNW GdYQHj; GdNW GdRNQaI; GdNW GdJMSjf(B.s
Title translation: 'Arabic calligraphy - Aesthetic theory and handicraft'- Shaker Laibi
Arabic
Keywords: Arabic Calligraphy; NK1648-1678 Religious art